RISK FACTORS FOR ATONIC POSTPARTUM HEMORRHAGE: A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
ABSTRACTIntroduction: Postpartum bleeding occurs in 3-10% of all deliveries. Although numerous causes exist, uterine atony is the most frequent, accounting for about 70% of all instances.Objective: This study aimed to identify and quantify risk variables for atonic postpartum hemorrhage. Methods: The databases PubMed, CINAHL, EMBASE, Web of Science, and ClinicalTrials.gov were searched for English language studies with no date or geographical constraints. Randomized trials, prospective or retrospective cohort studies, and case-control studies of pregnant individuals who suffered atonic postpartum hemorrhage and reported at least one risk factor were included in the studies. This review contained 16 studies out of the 1,977 records evaluated. A qualitative synthesis of research with low and moderate risk of bias rates each risk factor as definite, likely, unclear, or not a risk factor.Results: This research found 47 potential risk factors for atonic postpartum hemorrhage, 15 of which were deemed definite or likely risk factors. The remaining 32 risk factors were unrelated to atonic postpartum hemorrhage or had inconsistent or inconclusive data.Conclusion: A significant proportion of postpartum bleeding occurs without known risk factors. Many risk variables for atonic hemorrhage contained in existing risk assessment tools were confirmed, with past postpartum hemorrhage of any cause, placenta previa, placental abruption, uterine rupture, and multiple pregnancies conferring the largest risk. Hypertension, diabetes, and ethnicity were new risk factors not previously included in risk-assessment systems. In this study, obesity and magnesium were not associated with to atonic postpartum hemorrhage.